Fuzzy programming approach for solving bi-level multi-objective linear programming problems - Tang, Wenguang; Zhao, Fenxia (2010 Seventh International Conference on Fuzzy Systems and Knowledge Discovery, 2010)
This paper presents a fuzzy programming approach for solving bi-level multi-objective linear programming problems with a single decision maker at the upper level and multiple decision makers at the lower level. The membership function for the vector of fuzzy-effective solution controlled by upper level as well as the membership functions for all the objective functions at the two levels are developed in the model. Then this approach is used to achieve the highest degree of each of the membership functions and abstain the satisfactory solution for all decision makers. Numerical examples are given to demonstrate the proposed approach.